Analysis of time to progression among patients with endometrial cancer stage III c - Dańska, Anna; Bidziński, Mariusz; Krynicki, Ryszard (Menopause Review/Przegląd Menopauzalny, 2004)
Objectives: Endometrial cancer is still one of the leading killers among women in Poland. Stage III c of this cancer although not very common gives unsatisfactory results of patients’ treatment. Design: Taking into consideration these facts the analysis of some histologic and clinical factors was performed in a group of patients with endometrial cancer stage III c. These parameters were correlated with time to progression. Material and methods: There were 30 patients selected to form the analyzed group. All patients had total hysterectomy with pelvic node dissection. In some cases of positive pelvic nodes, paraaortic lymphadenectomy was subsequently performed. Age, duration of symptoms, co-morbidity, histology type, grading, and other clinical parameters were correlated to assess the risk of recurrence. Results: It appeared that not optimal debulking of grossly involved nodes had a significant influence on time to progression. Optimal debulking causes mean 28 months free of disease as compared with 8 months in patients not optimally debulked. Serous or clear cell types of cancer and simultaneous involvement of pelvic and paraaortic nodes had also a negative prognostic value. Contrary to the use of postoperative radiochemotherapy, in which case time to progression was prolonged. Conclusions: It should be noted that radiochemotherapy in patients with endometrial cancer stage III c is a very helpful therapeutic option after complete surgery. Full dissection of grossly involved lymph nodes have a significant influence on treatment results.